Polyphenol-rich diet is associated with decreased level of inflammatory biomarkers in breast cancer patients - Agnieszka Sut; Maria Pytel; Marek Zadrozny; Jacek Golanski; Marcin Rozalski (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. The study investigated the relationship between dietary intake of polyphenols and inflammatory markers: CRP, neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), medium platelet volume/lymphocyte ratio (MPVRL), in newly-diagnosed breast cancer patients. Objectives. The aim of this work was to verify whether diet rich in plant polyphenols affects inflammatory markers in breast cancer patients. Materials and methods. 78 patients (55.3±14.5 years) treated surgically for breast cancer were studied. A modified FFQ and authorial worksheet based on the Phenol Explorer database was used to measure the amount of plant polyphenols in a diet. Basing on the median of polyphenols intake (1780 mg/day), the group was divided into two subgroups: low- and high- dietary intake of polyphenols (LDIP and HDIP, respectively). Plasma CRP level was measured and NLR, PLR and MPVLR were calculated using results from peripheral blood morphology. Results. LDIP was associated with significantly higher CRP (elevated in 34.5% LDIP patients vs. 8.3% HDIP, p<0.003), NLR (elevated in 46.2% LDIP patients vs. 25.6% HDIP, p<0.006) and PLR level (elevated in 25.6% LDIP patients vs. 12.8% HDIP, p<0.03). MPVLR was not significantly different between both the subgroups. Conclusion. High dietary intake of polyphenols remarkably reduced process of inflammation in breast cancer patients, which has important clinical implications. The study demonstrated also an usefulness of simple, cheap and commonly available biomarkers for monitoring anti-inflammatory effects of diet.